The efficacy of intravenous clonidine premedication to reduce surgical area bleeding in posterior lumbar spine fusion surgery - Rajkumar, Suresh; M, Senthil; Ezhilrajan, V (International Journal of Medical Research and Review, 2016)
Background: A posterior lumbar spine fusion surgery always associated with significant amount of blood loss and requires blood transfusion. The purpose of this study is to evaluate the efficacy of intravenous clonidine premedication to achieve bloodless surgical field and decrease the need for blood transfusion by controlled hypotension. Methods: Sixty patients scheduled for posterior lumbar fusion surgery were included in this randomized placebo controlled trail. Patients were classified into two groups: Group 1 received intravenous clonidine 3 µg/kg by infusion over 15 minutes before surgery and Group 2 received placebo as same. Hemodynamic variables, quality of surgical field by bleeding severity score, estimated amount of blood loss, duration of surgery and any blood transfusion were analyzed. Results: Heart rate and mean arterial pressure found less in clonidine group than placebo but not significant. The estimated blood loss (390.8±99.99 mL vs 741.13±79.90 mL; P = 0.001*) and duration of surgery (160.67±16.91 vs 205.9±16.72 min, P=0.001*) were significantly less in clonidine group compared to placebo. The quality of surgical field was better in clonidine group than placebo at all times. No cases of severe bradycardia or clinically significant hypotension were observed in clonidine group. Conclusion: Premedication with intravenous clonidine 3 µg/kg found clinically safe & effective drug in controlling blood loss and improves quality of surgical field in posterior lumbar fusion surgeries as a sole agent.